(3GdEYdGe HCYdGe HjJ GGddg GdMQGes - (3eMeO Hf CMeO Hf eMeO Hf bGVj NGf eMehO GdfgQhGdj GdMfaj Gdecj , bWH GdOjf,J (B988 (3g` s ((3ESeGYjd Hf JQci Hf CMeO GdefTdjdi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdeSLO GdMQGe MQekG BefG heKGHg GdfGS CdN CeG HYO , adeG habfi Gddg dNOeI GdYde GdTQja hLYdfi s
(3BNQgG (B:s
(3eGdG fLe Ydi Gab GdSeGA heG gH GdZSje Ydi GdYTGb HGdWjH hGdMeO ddg QH GdYGdejf hcGf GdaQGZ ef s
(3GfXQ Qbe (B45 (3JGQjNs
(3GgOGg Edi GdSdWGf eQGO NGf GdYKeGfis
(3hCJe JCdjag SfI (B985s
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B17s
Keywords: (3GdJGQjNs